Texts Of Special Powers And General Powers Of Attorney Forensic Linguistic Study - juliarta, I Made; Wirawan, I Gede Nika (Denpasar Institute, 2024)
A power of attorney is a document that gives authority to another party to carry out legal actions, for and on behalf of the person giving the power of attorney. Power of attorney consists of special power of attorney and general power of attorney. A special power of attorney explains what actions the recipient of the power can take. This research analyzes the situational context in the text of a notarial deed agreement and the differences between the text of a special power of attorney and a general power of attorney. This research uses functional systemic linguistic theory proposed by Halliday (2004), meaning semantics and forensic linguistic theory proposed by Olsson (2008). Qualitative research methods are used to describe a phenomenon in depth and are carried out by collecting data. Qualitative methods use observation of phenomena and research more into the substance of the meaning of the phenomenon. This method is used to analyze the context of the situation contained in the text using the theory put forward by Halliday (2002). Data were analyzed using situational context theory proposed by Halliday (2004). Data were analyzed using situational context theory which analyzes the field, participants and text modes used in the agreement letter between the authorizer and the recipient. This research shows that the text is dominated by a relational process which aims to provide information about agreements and agreements in the text of the notarial deed. The text is dominated by verbs that express relational processes